2004
DOI: 10.1100/tsw.2004.207
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Prevents Ibuprofen-Induced Gastric Mucosal Lesions and Influences Endogenous Antioxidant Status of Stomach in Rats

Abstract: Recently, free radical—induced tissue damage is implicated in the nonsteroidal anti-inflammatory drugs (NSAIDs)—involved gastric mucosal lesion. Administration of taurine, an endogenous antioxidant, is reported to be beneficial in various clinical conditions. Therefore, we decided to study the protective effect of taurine in ibuprofen-induced gastropathy and the effects of administration of taurine on the endogenous antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…Balasubramanian et al have already reported the formation of free radicals in the gastric mucosa of ibuprofen-induced rats. 28 Pre-treatment of glucosamine significantly maintained the activities of membrane bound ATPases by the counteraction of ibuprofen-induced free radicals by the free radical scavenging property of glucosamine. 29 Histopathological investigations showed that ibuprofen administration was characterized by cell damage (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Balasubramanian et al have already reported the formation of free radicals in the gastric mucosa of ibuprofen-induced rats. 28 Pre-treatment of glucosamine significantly maintained the activities of membrane bound ATPases by the counteraction of ibuprofen-induced free radicals by the free radical scavenging property of glucosamine. 29 Histopathological investigations showed that ibuprofen administration was characterized by cell damage (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…By blocking ion channels (mainly calcium) within a cell, lead causes autonomic system dysfunction resulting in increased hydrochloric acid secretion and mucosal erosion [25][26][27]. There are reports indicating that the primary pathogenetic factors in ulcers are free radicals [28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Such antidote effects of taurine or high capacity for taurine uptake into the cells (or conversely harmful effects of taurine depletion) have i.a . been found against alcohol (2340), against the analgesic and fever-depressing drug acetaminophen (also called paracetamol) (4144), against the aminoglycoside antibacterial drug gentamicin (4547), against the immunosuppressant drug cyclosporine A (48, 49), against the anticancer drugs cisplatin (5054), doxorubicin (also called adriamycin) (5562), bleomycin (6378), methotrexate (79) and taumustine (80), against the cytokine interleukin-2 (IL-2), which is used for immunotherapy of cancer (8184), against the estrogen receptor modulator tamoxifen, which is used in therapy of breast cancer (8587), against the antiarrhythmic drug amiodarone (88), against the beta -adrenergic agonists isoproterenol (55) and isoprenaline (8992), against nicotine (9395), against oxidized low-density lipoprotein (LDL) (96), against oxidized fish oil (97), against high glucose levels (96, 98110), against fructose (111122), against galactose (123), against advanced glycation end-products (AGEs) (100, 124, 125), against homocysteine (126–130), against the anti-inflammatory drugs ibuprofen (131) and indomethacin (132, 133), against the herbicide paraquat (65, 134, 135), against carbon tetrachloride (136149), against menadione (150), against 1,4-naphtoquinone (137, 139), against hydrazine (137, 139), against trinitrobenzene sulfonic acid (151, 152), against acrylonitrile (153), against perchloroethylene (154), against methylene dianiline (155), against arsenic (156164), against cadmium (…”
Section: Evidence Showing That Taurine Functions As a Biological Antimentioning
confidence: 99%